(untitled) (Nigerian Journal of Pharmaceutical Research, 2024)
Background: Metformin is a biguanide antihyperglycemic drug used with diet and exercise for glycemic control in type 2 diabetes mellitus. Objectives: This research aims to compare and analyze different metformin products to ascertain their critical quality parameters. The goal is to ensure that prescribed medicine effectively treats patients and protects the public. Materials and Methods: We evaluated the quality of ten metformin tablet brands in Lagos (Mushin and Surulere area) using official methods to assess weight, hardness, friability, disintegration time, and dissolution. Active ingredient content was also measured. Results: Out of all the tablets tested, only 10 % had weights outside of the official British Pharmacopoeia 2002 limits (not more than two tablets should deviate from ±5% and none of the tablets should deviate by ± I0). The hardness test was passed by all the tablets (A minimum hardness of 4 kgF is a pass), while 80 % passed the friability test (weight loss of ≤ 1 %w/w is a pass). Additionally, all film-coated tablets disintegrated within 30 minutes according to United States Pharmacopoeia/National Formulary 2003 (film-coated tablets disintegrate within 30 minutes). Ninety percent of the tablets passed the dissolution test (drug release within 60 minutes should be between 93 and 103 %) and 90 % of all brands examined passed the assay test for the active ingredient contents. The British Pharmacopoeia 2019 standard was used for the dissolution test. Conclusion: Routine pharmaceutical analysis is essential for the quality of pharmaceutical products and the safety of consumers.